(untitled) - Stabler, Mike (New York, 2010)
Making a key contribution toward understanding tourism, this book examines how the business operates in global contexts, the effects of tourism on destination areas and the interaction between it and natural environments.
Keywords: Tourism,Leisure,Du lịch,Giải trí; Marketing,Economic aspects,Tiếp thị,Khía cạnh kinh tế; Great Britain,Anh